Tooth brushing, oil pulling and tissue regeneration: A review of holistic approaches to oral health - Singh, Abhinav (Medknow Publications Pvt Ltd, 2011)
Even though dentistry was not a specialized branch of Ayurveda, it is included in its Shalakya Tantra (system of surgery). Problems such as deformities of the oral cavity, plaques and infections were managed in ancient India. Traditional medicine can treat various infectious and chronic conditions. Research has shown that all kinds of chewing sticks described in ancient Ayurveda texts have medicinal and anti-cariogenic properties. Its oil pulling (Kaval, Gandush) practice is claimed to cure about 30 systemic diseases. Amla (Emblic myrobalan), is a general rebuilder of oral health. Bilberry fruit (Vaccinium myrtillus) and hawthorn berry (Crateagus oxycanthus) stabilize collagen, strengthening the gum tissue. Liquorice root (Glycyrrhiza glabral) promotes anti-cavity action, reduces plaque, and has an antibacterial effect. Use of safe, quality products and practices should be ensured based on available evidence if traditional medicine is to be acknowledged as part of primary health care. Scientific validations of the Ayurveda dental health practices could justify their incorporation into modern dental care. Publicity of these techniques using appropriate media would benefit the general population by giving more confidence in the ancient practices, thus preventing tooth decay and loss.